2002
DOI: 10.1063/1.1499514
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of polycrystalline silicon gate deposition with HfO2 and Al2O3/HfO2 gate dielectrics

Abstract: Polycrystalline-silicon (poly-Si) gate compatibility issues with HfO2 and Al2O3 capped HfO2 gate dielectrics are reported. It can be generally stated that chemical vapor deposition (CVD) silicon gates using silane deposited directly onto HfO2 results in electrical properties much worse compared to similar HfO2 films using platinum metal gates. However, depositing CVD silicon gates directly onto Al2O3 capped HfO2 showed greater than a 104 times reduction in gate leakage compared to the poly-Si/HfO2 and poly-Si/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…[11±14] In the case of CVD, oxygen-containing chemicals such as b-diketonates, [15] hafnium nitrate, [16] hafnium tert-butoxide, [8,9] and mononuclear alkoxide complexes such as Hf(O t Bu) 2 (mmp) 2 , and Hf(mmp) 4 (mmp = 1-methoxy-2-methyl-2-propanolate, OCMe 2 -CH 2 OMe), [10,17,18] can be regarded as the most common class of the metal precursors. In the case of ALD, halide precursors have been used.…”
Section: Introductionmentioning
confidence: 99%
“…[11±14] In the case of CVD, oxygen-containing chemicals such as b-diketonates, [15] hafnium nitrate, [16] hafnium tert-butoxide, [8,9] and mononuclear alkoxide complexes such as Hf(O t Bu) 2 (mmp) 2 , and Hf(mmp) 4 (mmp = 1-methoxy-2-methyl-2-propanolate, OCMe 2 -CH 2 OMe), [10,17,18] can be regarded as the most common class of the metal precursors. In the case of ALD, halide precursors have been used.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Van Dover and co-workers have reported Zr 0.62 Al 0.38 O 1.8 thin film in which the crystallinity starts to appear at 850°C. 14 Accommodation of Al 2 O 3 layer with HfO 2 films in order to increase the interfacial stability with Si has been reported recently, 8,9 and some thermal stability studies on Hf-Al-O films have also been reported recently. 15 Electrical properties such as electron trapping and band alignment in amorphous Hf-Al-O have also been reported.…”
mentioning
confidence: 99%
“…A convenient approach for depositing such films ͑oxides and mixed oxides͒ is the atomic layer deposition ͑ALD͒ technique, where self-saturating surface chemical reactions are employed. This approach 5,6 has been successfully applied to control chemical reactions at the Si/ high-k and high-k / gate electrode interfaces, as well as to obtain ͑HfO 2 ͒ x ͑Al 2 O 3 ͒ 1−x structures retaining sufficiently high dielectric constant and remaining amorphous up to high processing temperatures. Metastable defect configurations owing to the low-temperature film deposition process can be suppressed by postdeposition annealing.…”
mentioning
confidence: 99%
“…[3][4][5] A good tradeoff between the characteristics of these two materials 1, [6][7][8][9][10][11] can be achieved by forming ͑HfO 2 ͒ x ͑Al 2 O 3 ͒ 1−x mixed oxides, either homogeneous in composition or in nanolaminated structures. A convenient approach for depositing such films ͑oxides and mixed oxides͒ is the atomic layer deposition ͑ALD͒ technique, where self-saturating surface chemical reactions are employed.…”
mentioning
confidence: 99%